2000
DOI: 10.1001/jama.283.5.617
|View full text |Cite
|
Sign up to set email alerts
|

Life Expectancy Gains From Cancer Prevention Strategies for Women With Breast Cancer and <EMPH TYPE="ITAL">BRCA1</EMPH> or <EMPH TYPE="ITAL">BRCA2</EMPH> Mutations

Abstract: Interventions to prevent second cancers, particularly PCM, may offer substantial LE gain for young women with BRCA-associated early-stage breast cancer. Estimates of LE gain may help women and their physicians consider the uncertainties, risks, and advantages of these interventions and lead to more informed choices about cancer prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
98
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(104 citation statements)
references
References 55 publications
(56 reference statements)
2
98
0
3
Order By: Relevance
“…There is some support for a substantial benefit of tamoxifen in prevention of contralateral tumours in mutation-positive breast cancer cases, from a retrospective casecontrol study (Narod et al, 2000). Simulation studies also suggest a secondary preventive effect (Schrag et al, 2000). Our results suggest a modest primary preventive effect, which is stronger in BRCA2 positive women than in BRCA1 positive.…”
supporting
confidence: 54%
“…There is some support for a substantial benefit of tamoxifen in prevention of contralateral tumours in mutation-positive breast cancer cases, from a retrospective casecontrol study (Narod et al, 2000). Simulation studies also suggest a secondary preventive effect (Schrag et al, 2000). Our results suggest a modest primary preventive effect, which is stronger in BRCA2 positive women than in BRCA1 positive.…”
supporting
confidence: 54%
“…Data to date from clinical trials are equivocal about the value of tamoxifen for chemoprevention in this population (Narod et al, 2000;Schrag et al, 2000;King et al, 2001;Robson, 2002). An important difference between these trials and the experiments performed here is that in the mouse model full-length Brca1 expression is lost, while in the human studies, the women have loss or mutation of just one allele in the majority of their normal-appearing mammary epithelial cells and loss or mutation of all BRCA1 function only in a subset of these cells or in the carcinomas (Cavalli et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to this, it has been hypothesized that tamoxifen, an SERM, might have a protective role at early stages of cancer progression even if the majority of cancers are ERa negative. Clinical studies published to date demonstrate mixed results (Narod et al, 2000;Schrag et al, 2000;King et al, 2001;Robson, 2002), where one study showed efficacy (Narod et al, 2000) and a second study, albeit with low tumor numbers, showed minor enhancement (King et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These apparent differences between family-based and population-based studies may have implications for therapeutic decision making. For instance, it has been proposed that the magnitude of life expectancy gains from cancer prevention strategies, including prophylactic contralateral mastectomy, strongly depends on the penetrance of the BRCA mutation (Schrag et al, 2000). Our results suggest that the penetrance with regard to contralateral disease isat least in our hospital-based sample -not necessarily a feature determined only by the nature or location of the BRCA mutation itself, as the mutational types and frequencies were similar in our patients with unilateral and bilateral breast cancer.…”
Section: Discussionmentioning
confidence: 99%